Optical dispersion parameters based on single-oscillator model and optical absorption of nanocrystalline metal phthalocyanine films: A comparison study - Farag, A. A. M.; Yahia, I. S.; AlFaify, S.; Bilgicli, Ahmet T.; Kandaz, M.; Yakuphanoğlu, Fahrettin (Academic Press Ltd- Elsevier Science Ltd, 2013)
Nanocrystalline thin films of {Co(II), Cu(II), Mn(III), Pb(II) and Zn(II)) phthalocyanine complexes were deposited by spin coating sol gel technique. The surface morphologies of the films are found to be dependable on the type of the metal complex. The absorption spectra of the films show two well defined absorption bands of phthalocyanine molecule; namely Soret (B-band) and Q-bands. The Q-band absorption of the phthalocyanine complexes shifts to longer wavelength with the central metal change. The analysis of the spectral behavior of the absorption coefficient (alpha) in the absorption region revealed two expected indirect transitions. The refractive index (n) and the absorption index (k) were calculated using the measured data of the transmittance T(lambda) and reflectance R(lambda) coefficients. The dispersion parameters such as dispersion energy (E-d), oscillator energy (E-o), high frequency dielectric constant (epsilon(infinity)'), and lattice dielectric constant (epsilon(L)) were determined using the single oscillator model. The main reason for the change in dispersion parameters of the phthalocyanine complexes may be attributed to the intensity of the metal coordination bonds that are dependent on the bound metal atoms due to their electronegativity change. The founded results of the nano-crystalline metal phthalocyanine thin films can be useful for optoelectronic applications. Discussion of the obtained results and their comparisons with the available published literature were also considered. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Metal phthalocyanine complex; AFM micrographs; Optical properties; Optical dispersion parameters; Comparison study